AMBULATORY BLOOD PRESSURE MONITORING INDICATORS IN MIDDLE-AGED AND ELDERLY HYPERTENSIVE PATIENTS UNDER COMBINED ANTIHYPERTENSIVE THERAPY - V.S. Pasko (State Institution of Science «Research and Practical Center of Preventive and Clinical Medicine» State Administrative Department, 2021)
It is known that arterial hypertension affects 30-35% of adult population of industrialized countries, and its prevalence reaches 40-50% among the elderly. In recent years, the issue of optimizing of treatment of hypertension in elderly people has been discussed such as choice of effective antihypertensive drugs with the least number of side effects, prevention of complications, reduced mortality, improvement of quality of life.